Natural Area Weeds: Chinese Tallow (Sapium sebiferum L.): SS-AGR-45/AG148, 7/2015 - Langeland, K.A. (EDIS, 2015)
Florida's natural areas—a great source of pride and enjoyment to its citizens—provide recreation, protect biodiversity and fresh water supplies, buffer the harmful effects of storms, and significantly contribute to the economic well-being of the state (Jue et al. 2001). Natural areas are protected in over ten million acres (nonsubmerged) of state, federal, local and private managed conservation lands in Florida (http://fnai.org). Unfortunately, many of these natural areas can be adversely affected by invasive plant species. An estimated 25,000 plant species have been brought into Florida for use as agricultural crops or landscape plants. While only a small number of these have become invasive, those that do can adversely affect native plant communities by competing for space and resources, disrupting hydrologic and fire regimes, or hybridizing with native species. They must be managed for the protection of native communities in natural areas. Chinese tallow (Triadica sebifera (L.) Small is one of these invasive plant species. Document first published in Dec. 2002.